La généralisation des activités à visée philosophique dans l’école, avec les élèves en difficulté : enjeux et projet - Jean-Charles Pettier (Recherches en Éducation)
What are the issues of a generalization in schools of the “Practices with philosophical aim” (PPA)? In this paper we wriggle out from the a priori charm of the PPA to examine in a philosophical manner the foundations and political project that could result from them. Doing so, we intend to give to teachers keys to guide their teaching. At the ethical level, we identify better to what extend the generalization of the PPA participate to the construction of human essence by means of the Right. An ethics of the Human Right, taking into consideration some contemporary philosophical criticisms (Sartre, Foucault, Heidegger), which contest the idea of any human essence, make by the generalization of PPA in schools, the intellectual tool to participate to this critical humanity whose responsibility is to elaborate the Right. The child, carrier-to-be of the human project, must learn how to reflect, for it is politically fundamental in a democracy of Rights. Her/his reflection is based on the development of her/his individual capacity to mobilize alert, complex, abstract and conceptual thinking. We widen, thanks to education, the field of her/his spontaneous questioning towards an authentic “philosophical citizenship”. Generalization of the PPA is bearing pupils’ success - some of them sometimes having school difficulties- by examining in a philosophical manner the school disciplines, by identifying better their nature and specific modalities, to finally situate and integrate them better. By means of the philosophical debate, we convey a political and social model which aims at, eventually, exempt from “communautarist” violence to the benefice of dialogue between cultures.